2015
DOI: 10.17583/remie.2015.1429
|View full text |Cite
|
Sign up to set email alerts
|

Developing Cooperative Learning through Tasks in Content and Language Integrated Learning

Abstract: This article presents the results of a study on teachers’ perceptions regarding specific work with tasks in the CLIL (Content and Language Integrated Learning) classroom, a context where academic content and a foreign language are learnt simultaneously. A questionnaire consisting of closed and open questions was administered to 25 teachers working in a school participating in an innovative project based on the implementation of tasks used as an instrument to promote cooperative learning. Following an interdisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In general, we can conclude that majority of the respondents have good perception of CL. Similar findings were reported by [27,30,33,37], who argue that CL increased their participants' motivation to learn in comparison to traditional lecture instruction due to the interactive and goal shared nature of the activities performed in class. [5] also found that working in teams where group members feel that their individual contributions are relevant to the group's success resulted in increased motivation to learn.…”
Section: Instructors' and Students' Perceptions Of CL Practicessupporting
confidence: 86%
See 3 more Smart Citations
“…In general, we can conclude that majority of the respondents have good perception of CL. Similar findings were reported by [27,30,33,37], who argue that CL increased their participants' motivation to learn in comparison to traditional lecture instruction due to the interactive and goal shared nature of the activities performed in class. [5] also found that working in teams where group members feel that their individual contributions are relevant to the group's success resulted in increased motivation to learn.…”
Section: Instructors' and Students' Perceptions Of CL Practicessupporting
confidence: 86%
“…There is consensus among CL reviewers that individual accountability and positive interdependence are actually essential components for successful CL [13]. CL is a teaching method, in which students of diverse background are assembled in groups to accomplish a common task [37]. It helps students to build rapport with other students [39].…”
Section: Background Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…CLIL also boosts teachers' self-esteem and motivation by triggering "rethinking of their teaching vision" (D'Angelo and García 2012: 76). In this context, teachers' perceptions of their actual performance may significantly affect their understanding of the challenges that CLIL entails (Halbach 2009;Ramos Ordóñez and Pavón 2015), how to construct teacher collaboration (Meyer 2010), and how to scrutinise teachers' profile and competences (D'Angelo and García, 2012;Hylliard 2001;Pavón and Ellison 2013). A lot of attention then has been given to reviewing teachers' opinions of their role in CLIL and a number of studies have specifically investigated teachers' perceptions of CLIL in different European contexts (Hüttner et al 2013 [Austria]; Infante, Benvenuto and Lastrucci 2009 [Italy];Moliner 2013;Pena and Porto 2008;Travé 2013 [Spain]; Viebrock 2012 [Germany]).…”
Section: Introductionmentioning
confidence: 99%